A light in the dark: the history and ethics of a therapeutic relationship - Lorettu, Liliana (Medicina Historica, 2019)
The therapeutic relationship is like a tailor-made dress: specific for the individual patient. Its objective is the well-being of the patient and the overcoming of his difficulties; in some cases the goal is to teach the patient to take care of himself. The therapeutic relationship can also have a positive value for the therapist, in the context of a reciprocity, which learns from the patient some teachings that he gives himself to the patient. In the therapeutic relationship there can be some issues linked to new and unexpected difficulties and which can be overcome with a careful examination of one’s defense mechanisms.